2011
DOI: 10.1007/s10534-011-9502-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary selenium regulation of transcript abundance of selenoprotein N and selenoprotein W in chicken muscle tissues

Abstract: Selenium (Se), selenoprotein N (SelN) and selenoprotein W (SelW) play a crucial role in muscle disorders. Se status highly regulates selenoprotein mRNA levels. However, few attempts have been performed on the effect of dietary Se supplementation on muscle SelN and SelW mRNA levels in birds. To investigate the effects of Se on the regulation of SelN and SelW mRNA levels in muscle tissues, one-day-old male chickens were fed either a commercial diet or a Se-supplemented diet containing 1.0, 2.0, 3.0 or 5.0 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Selenium has been recognized as a nutritional essential trace element that is important in many biological processes in mammals and birds (Holben and Smith, 1999;Surai, 2000). It has a crucial role in embryonic and postnatal development (Surai, 2000;Fortier et al, 2012), immunity, reproduction, antioxidant system (Choct et al, 2004;Juniper et al, 2011), and muscle function (Ruan et al, 2012;Zhang et al, 2012) and is known as a natural antioxidant (Surai, 2002). In poultry as well as in other animal species, Se can be added to diets through its mineral or organic forms, which represent the crucial factor that determines its metabolic fate (Suzuki, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Selenium has been recognized as a nutritional essential trace element that is important in many biological processes in mammals and birds (Holben and Smith, 1999;Surai, 2000). It has a crucial role in embryonic and postnatal development (Surai, 2000;Fortier et al, 2012), immunity, reproduction, antioxidant system (Choct et al, 2004;Juniper et al, 2011), and muscle function (Ruan et al, 2012;Zhang et al, 2012) and is known as a natural antioxidant (Surai, 2002). In poultry as well as in other animal species, Se can be added to diets through its mineral or organic forms, which represent the crucial factor that determines its metabolic fate (Suzuki, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Wilson et al, 1992;Holben & Smith, 1999). Thioredoxin reductase regulates cell growth(Mustacich & Powis, 2000), while selenoprotein N is responsible for normal muscle development(Zhang et al, 2012).…”
mentioning
confidence: 99%
“…28 The essential micronutrient Se, which exerts its antioxidant and anti-inflammatory properties in the form of selenoproteins such as glutathione peroxidase 3, selenoprotein P1 and thioredoxin reductase, has been shown to be protective in various inflammatory-based disease models. [29][30][31] A recent study in mice showed that Se in the form of selenoproteins played an indispensable role in uterine smooth muscle contractions, and the absence of any of these proteins affected the uterine contractility. 32 In vitro study of Se supplementation demonstrated that selenite suppresses key mediators involved in inflammation-induced activation of mediators involved in active labour in human fetal membranes and the myometrium.…”
Section: Clinical Importancementioning
confidence: 99%